Novel treatment strategy for Japanese newborns with high serum unbound bilirubin. Issue 1 (11th December 2012) - Yokota, Tomoyuki; Morioka, Ichiro; Kodera, Takayuki; Morisawa, Takeshi; Sato, Itsuko; Kawano, Seiji; Koda, Tsubasa; Matsuo, Kiyomi; Fujioka, Kazumichi; Morikawa, Satoru; Miwa, Akihiro; Shibata, Akio; et al.
Abstract Background Serum unbound bilirubin (UB) is a measure of bilirubin not bound to albumin, and has been reported to be better than total bilirubin level at identifying infants at risk of developing bilirubin‐induced neurotoxicity, including auditory abnormalities. A detailed treatment strategy for newborns with high serum UB has not been established. The aim of this study was to assess auditory outcomes in newborns with serum UB ≥1.00 μg/dL who were treated according to a novel treatment protocol. Methods A prospective clinical study was conducted in newborns weighing >1500 g with serum UB ≥1.00 μg/dL who were admitted to Kobe University Hospital and Kakogawa Municipal Hospital, Japan from 2006 to 2011. Enrolled newborns were treated as follows: (i) if serum UB was 1.00–1.50 μg/dL, phototherapy and infusion were given with or without albumin or immunoglobulin therapy; and (ii) if serum UB was >1.50 μg/dL, exchange transfusion was performed immediately. Auditory brainstem responses were evaluated at the time of discharge. Results A total of 89 Japanese newborns with UB ≥1.00 μg/dL were enrolled at a median age of 4 days. Of these, 85 had UB 1.00–1.50 μg/dL and four had UB >1.50 μg/dL. After being treated according to the protocol, no newborns were diagnosed with auditory brainstem response abnormalities. Conclusions The present treatment protocol for Japanese newborns with serum UB ≥1.00 μg/dL may be useful for the prevention of bilirubin‐induced auditory abnormalities.